1998
DOI: 10.1111/1467-9566.00099
|View full text |Cite
|
Sign up to set email alerts
|

Recall Bias in Self‐reported Childhood Health: Differences by Age and Educational Level

Abstract: This study examines the impact of recall bias on self-reported childhood health. In a population of people aged from 25 to 74 years , childhood health was assessed retrospectively to explore its influence on socio-economic inequalities in adult health. Data were obtained from a postal survey in the baseline of a prospective cohort-study (the Longitudinal Study on Socio-Economic Health Differences in The Netherlands). Childhood health was measured as self-reported periods of severe disease in childhood. Relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Drawing from the extant literature, we examined several reasons why persons might change their childhood health rating, falling into three themes: demographic and socioeconomic background, early-life events, and later-life events. Beginning with demographic and socioeconomic background, and consistent with prior research, we found that maintaining the same rating was more likely for women and those higher on socioeconomic status (Matthews and MacLeod 2005; Van de Mheen et al 1998; Zajacova and Dowd 2011). …”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Drawing from the extant literature, we examined several reasons why persons might change their childhood health rating, falling into three themes: demographic and socioeconomic background, early-life events, and later-life events. Beginning with demographic and socioeconomic background, and consistent with prior research, we found that maintaining the same rating was more likely for women and those higher on socioeconomic status (Matthews and MacLeod 2005; Van de Mheen et al 1998; Zajacova and Dowd 2011). …”
Section: Discussionsupporting
confidence: 87%
“…Persons who experienced relatively little decline in memory and who had higher overall memory were more likely to maintain the same rating of their childhood health—a finding consistent with prior studies (Haas 2007; Van de Mheen et al 1998). Those who experienced the steepest declines in memory between survey waves altered their childhood health rating, either positively or negatively.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations